2020
DOI: 10.3390/molecules25020362
|View full text |Cite
|
Sign up to set email alerts
|

New Zampanolide Mimics: Design, Synthesis, and Antiproliferative Evaluation

Abstract: Zampanolide is a promising microtubule-stabilizing agent (MSA) with a unique chemical structure. It is superior to the current clinically used MSAs due to the covalent nature of its binding to β-tubulin and high cytotoxic potency toward multidrug-resistant cancer cells. However, its further development as a viable drug candidate is hindered by its limited availability. More importantly, conversion of its chemically fragile side chain into a stabilized bioisostere is envisioned to enable zampanolide to possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Several total syntheses of (−)-zampanolide ( 1 ) have been reported since the pioneering work of Smith and co-workers on (+)-zampanolide, , which had established the absolute configuration of natural zampanolide as 11 S , 15 S , 19 S , 20 S . Part of the chemistry developed in the context of these total syntheses has also served as a basis for the preparation of analogs for SAR studies. While these studies have shown that mono­(macro)­cyclic analogs lacking the C 3 bridge between C(11) and C(15) can retain sub-μM antiproliferative activity, they are still substantially less potent than the natural product. , At the same time, recent work from our own group has demonstrated that the removal of the C(13) methylene group (see also ref ) or the complete replacement of the tetrahydropyran ring by a suitably substituted morpholine moiety is well tolerated, with the corresponding analogs still exhibiting nanomolar IC 50 values for the inhibition of cancer cell growth in vitro .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several total syntheses of (−)-zampanolide ( 1 ) have been reported since the pioneering work of Smith and co-workers on (+)-zampanolide, , which had established the absolute configuration of natural zampanolide as 11 S , 15 S , 19 S , 20 S . Part of the chemistry developed in the context of these total syntheses has also served as a basis for the preparation of analogs for SAR studies. While these studies have shown that mono­(macro)­cyclic analogs lacking the C 3 bridge between C(11) and C(15) can retain sub-μM antiproliferative activity, they are still substantially less potent than the natural product. , At the same time, recent work from our own group has demonstrated that the removal of the C(13) methylene group (see also ref ) or the complete replacement of the tetrahydropyran ring by a suitably substituted morpholine moiety is well tolerated, with the corresponding analogs still exhibiting nanomolar IC 50 values for the inhibition of cancer cell growth in vitro .…”
mentioning
confidence: 99%
“…When inspecting the tubulin-bound structure of (−)-zampanolide (1), 4 it is immediately obvious that C(10), C (11), O(11′), C (15), and C( 16) are all in the same plane (as for all 2,6-syn-disubstituted tetrahydropyran-based systems with the 2 and 6 substituents in an equatorial orientation). This situation is recapitulated in meta-substituted 5-or 6-membered aromatic rings, except that bond angles are slightly different from those in THP-based systems, which leads to not exactly superimposable positions of the atoms attached to the ring.…”
mentioning
confidence: 99%
“…In light of its intriguing structural features and its potentially medically relevant biological activity, it is not surprising that (−)-zampanolide ( 1 ) has been the target of several total syntheses; in addition, a number of analogs have been prepared for SAR studies, , although the SAR of 1 is still underexplored. Different approaches toward the zampanolide macrocycle have been pursued as part of the different total syntheses of 1 , but the attachment of the sorbamide segment of the side chain in general has relied on the DIBALH , or Brønsted acid promoted “aza-aldol” reaction between (−)-dactylolide ( 2 ) and ( Z,E )-sorbamide ( 3 ) (Scheme ).…”
mentioning
confidence: 99%
“…Thus, natural products can also serve as architectural blueprints for validated pharmacophores that inspire and guide medicinal chemistry efforts toward new and effective antineoplastic agents suitable for clinical development. 6 As a class of natural products, steroids have a proven track record in drug discovery. The core ABCD ring system consisting of 17 carbons has provided a validated pharmacophoric template for designing biologically active small molecules.…”
mentioning
confidence: 99%
“…Subsequent studies from Eisai, however, revealed that truncated analogs that contained the eastern half of halichondrin B retained potent inhibitory cell growth in vitro and antitumor activity in vivo . , This synthetically tractable analog was eventually developed into the drug eribulin. Thus, natural products can also serve as architectural blueprints for validated pharmacophores that inspire and guide medicinal chemistry efforts toward new and effective antineoplastic agents suitable for clinical development …”
mentioning
confidence: 99%